(untitled) (Journal of Human Sciences, 2024)
This research aims to demonstrate the accuracy of the jurisprudential thinking of Muslim scholars, as they were not merely transmitting what they had learned; Rather, they presented problems and questions, and sought answers to them, and among those who had the upper hand in this matter: Al-Qarafi in his book Al-Thakhira, where he mentioned a number of problems in the various chapters of jurisprudence, so this research came to present examples of these problems, following the analytical approach that begins By understanding the problem and ending with answering it in different path.